A Good Night’s Sleep: Learning About Sleep From Autistic Adolescents’ Personal Accounts - Pavlopoulou, Georgia (Frontiers in Psychology, 2021)
Background Sleep is a strong predictor of quality of life and has been related to cognitive and behavioral functioning. However, research has shown that most autistic people experience sleep problems throughout their life. The most common sleep problems include sleep onset delay, frequent night-time wakings and shorter total sleep time. Despite the importance of sleep on many domains, it is still unclear from first-hand accounts what helps autistic people to sleep. The purpose of this study is to explore together with autistic adolescents their sleep-related practices before bedtime and during the day which contribute to a good night’s sleep. Methods Fifty-four autistic adolescents collaborated with an academic researcher in a novel adapted photo-elicitation methodology, rooted in a Lifeworld framework. The adolescents were invited to collect and analyze their data. The data were also presented in a community knowledge exchange event. Results Several self-reported practices that facilitate better nocturnal sleep were identified. Those were organized into two thematics: Evening/bedtime factors and Day time factors. These included practices such as personalized sensory and relaxation tools before bed and during night-time, engaging in a range of physical activities during daytime and accommodating personal time to engage with highly preferred and intense focus activities and hobbies. It also included spending time in predictable and fun ways with family members before bedtime. Conclusion This is the first time that a study uses a novel methodological approach based on personal accounts elicited by photos rooted in a Lifeworld framework to describe personal sleep-related practices before bedtime and during the day to identify a “good night of sleep” in autistic adolescents. The outcomes from the current study showed that sleep facilitating factors are in a direct contrast to the sleep hygiene recommendations. Therefore, it is thus important for the sleep practitioners and healthcare providers to move beyond providing standardized sleep hygiene interventions. A Lifeworld led care model that pays attention to personal experiences, promotes sense of agency, evaluates both autism-specific strengths and struggles could and should complement biomedical approaches. Lay Summary This is the first study to examine autistic adolescents’ self-reported sleep habits and factors which facilitate autistic adolescents’ sleep by employing adapted photo-elicitation interviews. This study is innovative in at least three ways. First, it examines the factors that may facilitate a good night’s sleep through personal accounts of autistic adolescents. Second, this is the first sleep study to adopt a collaborative, flexible approach to understanding positive sleep factors in the lives of autistic adolescents. This study employed a personalized approach into collecting, categorizing, coding, and analyzing qualitative data allowing autistic adolescents and the researcher to work together across key stages of data collection and data analysis. Third, we adopted a theoretical framework that allows us to consider autistic adolescents in both agency and vulnerability positions when it comes to their sleep difficulties. Our results highlight that sleep should be treated individually and in relation to the environmental and personal factors that affect each autistic person. Hence, researchers and professionals may benefit from working collaboratively with autistic adolescents with the aim to identify individual strengths and adopt a positive narrative around sleep. Furthermore, it is important to further examine both the daytime and evening factors that may affect bedtime and the quality and quantity of sleep as well as the role of intense focused interests and physical activities that cultivate positive feelings and help autistic people to relax before bedtime.